Preparation and Numerical Optimization of TiO2:CdS Thin Films in Double Perovskite Solar Cell - Ghazi Aman Nowsherwan; Aurang Zaib; Aqeel Ahmed Shah; Mohsin Khan; Abdul Shakoor; Syed Nizamuddin Shah Bukhari; Muhammad Riaz; Syed Sajjad Hussain; Muhammad Ali Shar; Abdulaziz Alhazaa (Energies, 2023)
This work focuses on preparing TiO2, CdS, and composite TiO2:CdS thin films for photovoltaic applications by thermal evaporation. The suggested materials exhibit very good optical and electrical properties and can play a significant role in enhancing the efficiency of the device. Various microscopy and spectroscopy techniques were considered to investigate the optical, morphological, photoluminescence, and electrical properties. FTIR confirms the material identification by displaying some peaks in the fingerprint region. UV Vis spectroscopy yields high transmission (80–90%) and low absorbance (5–10%) within the spectral region from 500 nm to 800 nm for the composite thin films. The optical band gap values for CdS, TiO2, and TiO2:CdS thin films are 2.42 eV, 3.72 eV, and 3.6 eV. XRD was utilized to analyze the amorphous nature of the thin films, while optical and SEM microscopy were employed to examine the morphological changes caused by the addition of CdS to TiO2. The decrease in the bandgap of the composite thin films was determined by the Tauc plot, which is endorsed due to the band tailing effects. Photoluminescence spectroscopy depicts several emission peaks in the visible region when they are excited at different wavelengths, and the electrical measurement enhances the material conductivity. Furthermore, the proposed electron transport materials (TiO2, CdS, TiO2:CdS) were simulated with different perovskite materials to validate their design by employing the SCAPS-1D program and assess their performance in commercial implementation. The observed results suggest that TiO2:CdS is a promising candidate to be used as an ETM in PSC with enhanced productivity.